The OSIS Chairman Election in the Pandemic Period - Tiyo Kurniawan; Siti Awaliyah (Randwick International of Social Science Journal, 2022)
This study aimed to describe socialization activities, implementation of elections, implementation constraints, and efforts to overcome obstacles in the implementation of the OSIS chairman election at SMA Negeri 2 Kediri. This study used a qualitative approach with descriptive type of research. Interviews, observations, and documentation were used as data collection techniques. Data analysis was carried out through several stages, namely data reduction, data presentation, and drawing conclusions. The results of the study show that the socialization of the election of the OSIS chairman is carried out online by distributing socialization materials through social media, conducting debates, and candidate campaigns. There are three stages of implementing the OSIS chairman election, namely candidate selection, voting and counting of votes, and submission of results. Obstacles in the implementation of the OSIS chairman election are such as delivery in form ation is not optimal, the enthusiasm of the participants decreased, difficult to coordinate, and signal interference. The solution to solve these problems is collaborated with other social media, conduct evaluations, and increase coordination activities in a small scope in the committee.